Daily rhythm of blood pressure at patients with autoimmune thyreoiditis depending on function of the thyroid gland - Ye. B. Kravets; Ye. M. Idrisova; V. N. Latypova; Damdindorj Davaasuren (Бюллетень сибирской медицины)
The purpose of research was to give the comparative characteristic of a daily profile and circadian rhythm of blood pressure at patients with autoimmune thyreoditis depending on function of a thyroid gland. 66 patients with autoimmune thyreoditis and 25 healthy examinees participated in research. The received results testify that the daily rhythm of arterial pressure at patients with autoimmune thyreoditis authentically depends on the functional characteristic of a thyroid gland. Infringements of circadian rhythm of systolic blood pressure «non-dipper» and excessive decrease of diastolic blood pressure at night are characteristic for patients with autoimmune thyreoditis.